2022
DOI: 10.1155/2022/2158644
|View full text |Cite
|
Sign up to set email alerts
|

Pyrocatechol Alleviates Cisplatin-Induced Acute Kidney Injury by Inhibiting ROS Production

Abstract: As one of the most common cancer chemotherapy drugs, cisplatin is widely used in cancer management. However, cisplatin-induced nephrotoxicity occurs in patients who receive this drug. This study is aimed at developing therapeutic agents that effectively alleviate the nephrotoxic effects during cisplatin treatment. We identified a compound named pyrocatechol (PCL) from a natural product library that significantly alleviated cisplatin-induced cytotoxicity in vitro. Pyrocatechol treatment substantially ameliorate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…In terms of mitochondrial dysfunction, cisplatin has been shown to have significant effects on that [43,55,56]. One of the mechanisms underlying cisplatin-induced mitochondrial toxicity is the generation of ROS, leading to oxidative stress-induced cell death, which is also a well-defined source of cisplatin-induced side effects [57][58][59]. In this regard and notably, Pt-ttpy does not function like typical Pt complexes, likely for cisplatin and Pt-tpy, as it neither induces general ROS nor mt specific ROS production in both cancer cell lines and primary tissue cells for short and long time (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of mitochondrial dysfunction, cisplatin has been shown to have significant effects on that [43,55,56]. One of the mechanisms underlying cisplatin-induced mitochondrial toxicity is the generation of ROS, leading to oxidative stress-induced cell death, which is also a well-defined source of cisplatin-induced side effects [57][58][59]. In this regard and notably, Pt-ttpy does not function like typical Pt complexes, likely for cisplatin and Pt-tpy, as it neither induces general ROS nor mt specific ROS production in both cancer cell lines and primary tissue cells for short and long time (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…20 However, for normal cells with slow division, the damage caused by cisplatin is mainly closely related to ROS. 21,22 Our in vitro and in vivo experiments have demonstrated that cisplatin can lead to increased ROS levels in muscle cells, and this cisplatin-induced ROS can be effectively cleared by YCF and NAC. This may be related to the active ingredients in YCF.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of mitochondrial dysfunction, cisplatin has been shown to have significant effects on that (37) (52,53). One of the mechanisms underlying cisplatin-induced mitochondrial toxicity is the generation of ROS, leading to oxidative stress-induced cell death, which is also a well-defined source of cisplatin-induced side effects (54) (55,56). In this regard and notably, Pt-ttpy does not function like typical Pt complexes, likely for cisplatin and Pt-tpy, as it neither induces general ROS nor mt specific ROS production in both cancer cell lines and primary tissue cells for short and long time (Fig.…”
Section: Discussionmentioning
confidence: 99%